Identifying Predictors and Its Relationship with Developing of Diabetic Foot Ulcer (DFU) among People with 2 Diabetes Mellitus: A Scoping Review - Yusron Amin; Haswita Haswita (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Diabetic foot Ulcer is one of the severe complication of diabetes mellitus that leading to increasing serious problem. Early detection was an appropriate effort to prevent deteriorate condition. The aims of this study was to Identifying predictors of diabetic foot ulcer among type 2 diabetic patients through a scoping review. This study design is a scoping review using journal database with entering keyword predictors, diabetic foot ulcer, diabetic patient. Articles selected were met its inclusion criteria. The result showed that 17 articles included from 170 articles, from which 8 articles are cross-sectional studies, 7 articles are retro-spective studies, as well as 2 articles are systematic review. The incidence of diabetic foot ulcer reached more than 11,6%, from which dominated by grade 1 and grade 2 DFU, The significant predictors of diabetic foot ulcer classified into three categories including diabetes complications, demografic characteristic, and self-care behavior. Peripheral arterial disease (PAD) as the dominant predictor of diabetes complication, duration of diabetes >10 years as the dominant predictor of demografic characteristic, and low diabetic foot-care practice as the dominant predictor of self-care behavior. Reducing impact of DFU could be achieved by optimizing self-care behavior through appropriate diabetic-care and foot-care management based on patients characteristic and diabetes complications.